Economic organization in Chinese society (Stanford University Press, 1972)
Finance in Ningpo : the "Ch'ien Chuang, Sericulture and silk textile production in Ch'ing China, Cotton culture and manufacture in early Ch'ing China, The high-level equilibrium trap : the causes of the decline of invention in the traditional Chinese textile industries , The commercialization of agriculture in modern China, The sociology of irrigation : two Taiwanese villages, Marketing on the Changhua plain, Taiwan, The inculcation of economic values in Taipei business families, Doing business in Lukang, Marketing and credit in a Hong Kong wholesale market, A small factory in Hong Kong : some aspects of its internal organization, Economic management of a production brigade in post-leap China.